2017
DOI: 10.1039/c7sm00982h
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional rotation of cholesteric droplets driven by UV-light irradiation

Abstract: We investigated the novel photo-induced dynamics of azobenzene-doped cholesteric (Ch) droplets coexisting with the isotropic (Iso) phase. When the hemispherical Ch droplets initially stuck to glass substrates were irradiated by UV-light, they were parted from the substrates due to the surface disordering caused by the photo-isomerization of azobenzene. Then, the spherical droplets floating in the Iso phase exhibited an unexpected motion - a continuous and unidirectional rotation along the light propagation dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…The reason for eliminating this mechanism as the main explanation for the Lehmann effect observed in the coexistence region is that the rotation velocity of the droplets is independent of the chemical nature and the concentration of the impurities present in the samples. On the other hand, it is not excluded that this mechanism played a role in the experiment of Bono et al 17 on the reversal of the sense of rotation of the droplets under strong UV illumination.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The reason for eliminating this mechanism as the main explanation for the Lehmann effect observed in the coexistence region is that the rotation velocity of the droplets is independent of the chemical nature and the concentration of the impurities present in the samples. On the other hand, it is not excluded that this mechanism played a role in the experiment of Bono et al 17 on the reversal of the sense of rotation of the droplets under strong UV illumination.…”
Section: Introductionmentioning
confidence: 94%
“…In addition they do not always predict the good sense of rotation of the droplets 14 . Another explanation suggested by a recent work by Bono et al 17 but not confirmed experimentally 7 -lies on the existence of a flux of dissolved impurities (solute) across the droplets that would be responsible for a chemo-mechanical torque analog to the thermomechanical one. This torque, first predicted by de Gennes 18 , has already been observed in Langmuir monolayers [19][20][21] , freestanding films of Smectic C liquid crystals 22 and cholesteric phases 23 .…”
Section: Introductionmentioning
confidence: 96%
“…The droplets with helical axis parallel to the temperature gradient exhibit pure director rotation whereas the droplets with helical axis perpendicular to the temperature gradient rotate as a single body . Bono et al found photodriven rotation of cholesteric droplets . Color displays have been demonstrated by dispersing CLC droplets into polymer matrices .…”
Section: Control Of the Helical Axis In Microdroplets And Microshellsmentioning
confidence: 99%
“…In other cases two phase regions involving a cholesteric phase and an isotropic liquid phase were studied to bring out effects specific for systems with macroscopic handedness such as Lehmanntype effects [2,3]. When studying those an external force such as temperature and concentration gradients or electric fields give rise to rotations of the director field in suitably chosen geometries, for example, with the helical axis in the cholesteric drops perpendicular to the bounding plates of the sample [7][8][9][10][11]. We note that the inverse effect [12] has also been observed [13].…”
Section: Introductionmentioning
confidence: 99%